Thermotolerant Yeast Strains Adapted by Laboratory Evolution Show Trade-Off at Ancestral Temperatures and Preadaptation to Other Stresses - Luis Caspeta (American Society for Microbiology, 2015)
ABSTRACT A major challenge for the production of ethanol from biomass-derived feedstocks is to develop yeasts that can sustain growth under the variety of inhibitory conditions present in the production process, e.g., high osmolality, high ethanol titers, and/or elevated temperatures (≥40°C). Using adaptive laboratory evolution, we previously isolated seven Saccharomyces cerevisiae strains with improved growth at 40°C. Here, we show that genetic adaptations to high temperature caused a growth trade-off at ancestral temperatures, reduced cellular functions, and improved tolerance of other stresses. Thermotolerant yeast strains showed horizontal displacement of their thermal reaction norms to higher temperatures. Hence, their optimal and maximum growth temperatures increased by about 3°C, whereas they showed a growth trade-off at temperatures below 34°C. Computational analysis of the physical properties of proteins showed that the lethal temperature for yeast is around 49°C, as a large fraction of the yeast proteins denature above this temperature. Our analysis also indicated that the number of functions involved in controlling the growth rate decreased in the thermotolerant strains compared with the number in the ancestral strain. The latter is an advantageous attribute for acquiring thermotolerance and correlates with the reduction of yeast functions associated with loss of respiration capacity. This trait caused glycerol overproduction that was associated with the growth trade-off at ancestral temperatures. In combination with altered sterol composition of cellular membranes, glycerol overproduction was also associated with yeast osmotolerance and improved tolerance of high concentrations of glucose and ethanol. Our study shows that thermal adaptation of yeast is suitable for improving yeast resistance to inhibitory conditions found in industrial ethanol production processes. IMPORTANCE Yeast thermotolerance can significantly reduce the production costs of biomass conversion to ethanol. However, little information is available about the underlying genetic changes and physiological functions required for yeast thermotolerance. We recently revealed the genetic changes of thermotolerance in thermotolerant yeast strains (TTSs) generated through adaptive laboratory evolution. Here, we examined these TTSs’ physiology and computed their proteome stability over the entire thermal niche, as well as their preadaptation to other stresses. Using this approach, we showed that TTSs exhibited evolutionary trade-offs in the ancestral thermal niche, as well as reduced numbers of growth functions and preadaptation to other stresses found in ethanol production processes. This information will be useful for rational engineering of yeast thermotolerance for the production of biofuels and chemicals.